Consensus control strategy of an inverter air conditioning group for renewable energy integration based on the demand response. Issue 14 (17th September 2018) - Wang, Beibei; Zhang, Tianwei; Hu, Xiaoqing; Bao, Yuqing; Su, Huiling
Abstract : In order to improve the degree of renewable energy integration, the demand response resource, especially on the air conditioning load side, has received attention. Currently, most of the control modes for air conditioners are centralised control, which is difficult to be applied to widely distributed air conditioning. The current studies focus on central air conditioning, but there are few studies on split‐type inverter air conditioning, even though inverter air conditioning has become the most common split air system on the market. With this background, this study designs a consensus control strategy on the basis of distributed control mode, which for inverter air conditioners. The strategy is used for renewable energy integration in the studied region. The test results of various cases reveal the following findings: (i) the strategy adapts to the widely distributed air conditioning, (ii) the strategy can guarantee a fair allocation of power imbalance and user comfort, (iii) the control strategy can adapt to the uncertainties of air conditioners and the urban microclimate while efficiently consuming renewable energy. Therefore, the proposed consensus control strategy has practical value.